The naughty mole : a book about obedience ([Hong Kong] : Time Life Asia, 1997)
"Without telling his parents, Ben the mole sets out alone on an exciting adventure in the snow. But things soon start to go wrong when he gets lost and then falls into an icy pond. Ben's lucky escape makes him decide that he will listen to his parents in future."--Cover.
Keywords: Values -- Juvenile literature; Obedience -- Juvenile literature